2016
DOI: 10.1017/s1368980016000689
|View full text |Cite
|
Sign up to set email alerts
|

Gender inequalities in excess adiposity and anaemia combine in a large double burden of malnutrition gap detrimental to women in an urban area in North Africa

Abstract: Objective: The nutrition transition has exacerbated the gender gap in health in the Middle East and North Africa region as the increase in excess adiposity has been much higher among women than men. This is not exclusive of the persistence of anaemia, generally also more prevalent among women. We assessed the magnitude and sociodemographic factors associated with gender inequality vis-à-vis the double burden of excess adiposity and anaemia. Design: Cross-sectional study, stratified two-stage cluster sample. BM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 45 publications
4
32
0
Order By: Relevance
“…Vuong et al demonstrated similar findings in 6766 NHANES patients; hemoglobin levels increased with increasing AC in both male and female patients [ 6 ]. Traissac et al reported that, in a non-CKD cohort of 1689 female patients and 930 male patients, the prevalence of anemia (hemoglobin < 12.0 g/dL) was significantly higher in females with BMI ≥ 25 kg/m 2 than in males with BMI ≥ 25 kg/m 2 [ 33 ]. Thus, in general, BMI and AC appear to be positively associated with hemoglobin levels in the non-CKD population.…”
Section: Discussionmentioning
confidence: 99%
“…Vuong et al demonstrated similar findings in 6766 NHANES patients; hemoglobin levels increased with increasing AC in both male and female patients [ 6 ]. Traissac et al reported that, in a non-CKD cohort of 1689 female patients and 930 male patients, the prevalence of anemia (hemoglobin < 12.0 g/dL) was significantly higher in females with BMI ≥ 25 kg/m 2 than in males with BMI ≥ 25 kg/m 2 [ 33 ]. Thus, in general, BMI and AC appear to be positively associated with hemoglobin levels in the non-CKD population.…”
Section: Discussionmentioning
confidence: 99%
“…Tunisia is a country emblematic of the MENA region undergoing the nutrition transition and currently features high prevalences of excess adiposity and nutrition related NCDs, especially in urban areas where obesity concerns a third of the women and about one man out of six [4, 14, 15]. Tunisia has long been one of the most advanced countries of the MENA region regarding gender legislation [16].…”
Section: Introductionmentioning
confidence: 99%
“…non-egalitarian division of household labour, lower expectations regarding education or professional insertion for women, gender constraints on physically active leisure activities or not completely gender neutral legislation. This partly underlies the marked gender inequality in overweight and obesity harmful to women, who, in this context, have been shown to be two to three times more prone to excess adiposity than men [1, 10, 15]. On the other hand, this phenomenon is not exclusive of the persistence of certain types of undernutrition partly linked to micro-nutrient deficiency, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This has resulted in some contexts, in a double burden of malnutrition resulting from the co-existence of excess adiposity and/or associated Noncommunicable diseases (NCDs) and undernutrition phenomena partly linked to micronutrient de ciencies, e.g. as documented for iron de ciency and anaemia [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…This USI programme achieved some success in reducing ID, in certain contexts ( [8]), but defaults in the process of salt iodization, were also sometimes shown to increase the risk of iodine excess (IE) [7,9]. Also, in the context of the nutrition transition, the salt-rich westernized diet which underlies the progression of hypertension [4,5,20,21]. As for control of iodine de ciency, mandatory salt iodization had been implemented in speci c areas since 1984, but the national USI program was adopted in 1995 and launched in 1996 [18,22].…”
Section: Introductionmentioning
confidence: 99%